Analysis of the Utilization of Hair Fibers as an Eco-Friendly Concrete Construction Material - Iqbal, M.; Bachtiar, Erniati; Gusty, Sri; Indrayani, Poppy; Marzuki, Ismail; Chaerul, Muhammad (ASTONJADRO, 2025)
The handling of human hair waste is still not optimal, as it is often discarded or burned, leading to environmental pollution. This research aims to utilize human hair waste as a mixture in normal concrete, resulting in a fiber-reinforced concrete product with marketable value, providing a more beneficial use compared to simply being disposed of or burned. The purpose of this study is to analyze the mechanical properties of concrete using human hair fibers. The mechanical properties to be analyzed include compressive strength, tensile splitting strength, and flexural strength. This research is based on laboratory experiments. The variations in the amount of fiber used in the study are 0.25%, 0.5%, 1%, and 1.5% of the cement weight in the concrete mix. Based on the results of mechanical property testing, it can be concluded that the optimal addition of 1% human hair fibers yielded a compressive strength of 22.86 MPa, tensile splitting strength of 2.69 MPa, and flexural strength of 4.13 MPa.